2002
DOI: 10.1097/00005537-200202000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Successful Cochlear Implantation in Prelingual Profound Deafness Resulting From the Common 233delC Mutation of the GJB2 Gene in the Japanese

Abstract: We identified 4 CI patients (26.7%) out of 15 children carrying the homozygous 233delC mutation. Intra- and postoperative evaluation of the auditory system revealed almost intact cochlear and retrocochlear auditory function in these 4 patients. Postoperative auditory testing indicates that their speech perception had become significantly higher in comparison with that of other prelingual CI patients. These results suggest that prelingual deaf children carrying the homozygous 233delC mutation of the GJB2 gene c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
2
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 22 publications
(34 reference statements)
2
44
2
1
Order By: Relevance
“…One might therefore expect the connexin 26 group to have worse speech perception and language development when compared to the other group. That this is not the case might therefore suggest, in agreement with Matsushiro et al [2002], that connexin 26 patients are less affected when matched for similar degree of hearing loss. However, we do not believe that this is the case as we have tried to compensate for these factors by using the linear model and language age in our study.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…One might therefore expect the connexin 26 group to have worse speech perception and language development when compared to the other group. That this is not the case might therefore suggest, in agreement with Matsushiro et al [2002], that connexin 26 patients are less affected when matched for similar degree of hearing loss. However, we do not believe that this is the case as we have tried to compensate for these factors by using the linear model and language age in our study.…”
Section: Discussionmentioning
confidence: 66%
“…However, little is known of the extent to which genetic factors associated with deafness affect language and speech acquisition. Successful cochlear implantation in children with profound prelingual deafness homozygous for the 233delC mutation in connexin 26 gene has been reported [Matsushiro et al, 2002]. In a study of 20 children with cochlear implants, Green et al [2002] concluded that cochlear implant recipients with GJB2-caused deafness read within 1 standard deviation of hearing controls better than other congenitally deaf cochlear recipients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Universal neonatal hearing screening programs are the current trend and have become popular in many countries (Govaerts et al 2001; Joint Committee on Infant Hearing 2000; Mehl and Thomson 2002;National Institutes of Health 1993), because it is thought that optimum language development requires early identification of hearing loss and early intervention (Yoshinaga-Itano et al 1998). Cochlear implantation has resulted in remarkable improvement in auditory skills and development of speech production for patients with profound hearing loss associated with GJB2 mutations (Fukushima et al 2002;Matsushiro et al 2002). It is clear that genetic testing to determine the cause of deafness facilitates prediction of the course of hearing loss and prognostication of language development.…”
Section: Introductionmentioning
confidence: 99%